Ensinando tópicos de natureza da ciência a partir de uma história do conceito de fóton no ensino médio - Sé, Daniel de Sento (2016)
The teaching and learning of physics undergo a caring period in which it is necessary to update the curriculum, inserting Modern and Contemporary Physics notions, because this area of knowledge, act different technological devices that are part of the basic education students in everyday. Meant to address conceptual, historical and philosophical aspects on topics of FMC and the Nature of Science, we propose a Didactic Sequence supported in theory of Conceptual Fields by Gérard Vergnaud, using schemes the History and Philosophy of Science and the Nature of Science to discuss the evolution concept (or conceptualizations) of the photon. For this, we will discuss some issues of Conteporânea modern physics, such as the photoelectric effect, the Compton effect, wave-particle duality, the experiment HBT and notions of Quantum Optics. After application, it was observed that the understanding of how science is constructed and how the concepts are formulated, such as the concept of the photon, has been expanded, contributing to scientific training and autonomy of students